Process evaluation of social development interventions of the Working for Water Programme in Mamathola and Great Letaba Projects - Mangoale, Nani Thereza (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009